2022
DOI: 10.1371/journal.ppat.1010956
|View full text |Cite
|
Sign up to set email alerts
|

The E46K mutation modulates α-synuclein prion replication in transgenic mice

Abstract: In multiple system atrophy (MSA), the α-synuclein protein misfolds into a self-templating prion conformation that spreads throughout the brain, leading to progressive neurodegeneration. While the E46K mutation in α-synuclein causes familial Parkinson’s disease (PD), we previously discovered that this mutation blocks in vitro propagation of MSA prions. Recent studies by others indicate that α-synuclein adopts a misfolded conformation in MSA in which a Greek key motif is stabilized by an intramolecular salt brid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 53 publications
2
9
0
Order By: Relevance
“…Additional differences include the presence of a salt bridge between residues E35 and K80 in the PD structure, whereas the stabilizing salt bridge is between residues E46 and K80 in the MSA structure. Recent findings have shown that this structural difference is responsible for distinct biological properties between the PD and MSA strain in both in vitro and in vivo models [ 16 , 17 ]. Finally, differences in N-terminal contributions are also likely to alter fibril kinetics and stability.…”
Section: Distinct α-Synuclein Strains Give Rise To Pd and Msamentioning
confidence: 99%
See 3 more Smart Citations
“…Additional differences include the presence of a salt bridge between residues E35 and K80 in the PD structure, whereas the stabilizing salt bridge is between residues E46 and K80 in the MSA structure. Recent findings have shown that this structural difference is responsible for distinct biological properties between the PD and MSA strain in both in vitro and in vivo models [ 16 , 17 ]. Finally, differences in N-terminal contributions are also likely to alter fibril kinetics and stability.…”
Section: Distinct α-Synuclein Strains Give Rise To Pd and Msamentioning
confidence: 99%
“…Finally, cell culture models have also been used to investigate differences in α-synuclein strain biology, with the notable ability to predict in vivo outcomes [ 17 , 28 , 30 , 31 ]. For example, PD patient samples do not transmit disease to TgM83 +/− mice, nor do they infect HEK293T cells expressing YFP-tagged α-synuclein.…”
Section: Distinct α-Synuclein Strains Give Rise To Pd and Msamentioning
confidence: 99%
See 2 more Smart Citations
“…Experimental evidence is needed to show how air pollution may influence the progression of α-syn pathology. We used a mouse model of progressive α-syn neuropathology [ [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] ] to evaluate the effects of ambient nPM exposure on (i) levels and spread of α-syn aggregates from the OB to interconnected brain regions, (ii) microglial activation and (iii) expression of glutamate receptor A1 (GluA1, encoded by Gria1 ), which is involved in learning and memory [ 37 ] and odor/olfaction memory process [ 38 ], which are relevant to PD symptoms of dementia and hyposmia. The nPM batches were collected at the same site in downtown Los Angeles, and were later shown to vary widely in activities as evaluated by induction of NF-κB in vitro and neurotoxic responses in vivo [ 28 ].…”
Section: Introductionmentioning
confidence: 99%